Primary central nervous system lymphoblastic B cell lymphoma located at cerebellum in a child: A case report and literature review - Xueliang Yang; Yanlong Duan; Chunju Zhou; Ling Jin; Ningning Zhang; Shuang Huang; Meng Zhang; Jing Yang; Yonghong Zhang (Wiley, 2021)
ABSTRACT Introduction Primary central nervous system lymphoma (PCNSL) is extremely rare in pediatric population. We reported a case of PCNSL in a 3‐year‐old girl and reviewed the literature in the past three decades. Case presentation A 3‐year‐old girl presented with gait disturbance. A contrast‐enhanced magnetic resonance image of the brain showed a solitary bulky mass in the left cerebellar hemisphere, hydrocephalus and cerebellar tonsillar hernia. Surgical resection was performed and the patient was diagnosed with primary central nervous system lymphoblastic B cell lymphoma. Then the patient received regular chemotherapy, including 6 cycles of chemotherapy containing high‐dose methotrexate (HD‐MTX). The patient remains alive 15 months after the diagnosis with no evidence of active disease, but suffered twice chronic subdural hematoma, which was treated by burr hole drainage. Conclusion Lymphoblastic B cell lymphoma is a rare histologic subtype of pediatric PCNSL. Chemotherapy containing HD‐MTX remains the most effective treatment. The patient should avoid head impact after surgical resection of the tumor to prevent chronic subdural hematoma.